2016
DOI: 10.2298/vsp140728040s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and self-assessment of the pharmacists' competencies using the global competency framework (GbCF) in Serbia

Abstract: GbCF might be considered as an instrument for the competencies' evaluation/selfevaluation and their improvement, accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Evidence showed that competency frameworks are an acceptable tool for the facilitation and evaluation of performance development [32][33][34][35] . However, investigating pharmacists' acceptance of a competency framework before its actual use in performance assessment is rarely studied 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that competency frameworks are an acceptable tool for the facilitation and evaluation of performance development [32][33][34][35] . However, investigating pharmacists' acceptance of a competency framework before its actual use in performance assessment is rarely studied 36 .…”
Section: Discussionmentioning
confidence: 99%
“…With the aim of investigating problems in the supply and distribution of medicines on the Serbian market from various standpoints, a shortened variant of the Delphi method-Panel of Experts-was used in the study [10,11]. Panel was organized with an emphasis on the exchange of opinions and experiences, but also as a "scientific approach to consensus" [12].…”
Section: Panel Of Expertsmentioning
confidence: 99%
“…Critical evaluation skills have been emphasized in the recent COVID-19 pandemic given the level of misinformation especially surrounding possible treatments such hydroxychloroquine with the potential to increase deaths from suicide as well as appreciably increase prices through shortages [ 13 – 15 ]. All these competencies represent key challenges facing healthcare professionals including community pharmacists today [ 16 ]. We are aware that the discipline of pharmaceutical care arose from dissatisfaction with previous practice norms and the pressing need for more competent healthcare professionals with comprehensive knowledge of the therapeutic use of medicines to improve the care of patients [ 17 ], and this will continue.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assessment is considered an important skill for development, and within professional practice, self-assessment is the foundation upon which the cycle of continuing professional development is built [ 27 , 28 ]. Through self-assessment, health professionals develop the ability to manage their self-improvement [ 16 , 29 ]. Whilst self-assessment is used to describe many types of activities, aspects of “self-rating” or “self-audit” used to assess knowledge or clinical performance would appear to be the most relevant to pharmacists [ 30 ].…”
Section: Introductionmentioning
confidence: 99%